Methodology and microeconomics in the early work of Hyman P. Minsky - Jan Toporowski (Levy Economics Institute of Bard College, 2006)
This paper reviews the recently published doctoral thesis of Hyman P. Minsky, summarizing its main contributions to methodology and microeconomics. These were aspects of economics with which Minsky is not usually associated, but which lie at the foundation of his later work. They include critical remarks on Cambridge economics. The paper then draws out some antecedents of Minsky's ideas in the work of Henry Simons, and highlights the Marshallian monetary analysis that he adopted.
Keywords: B22; D2; E12; E50; 330; Minsky; Schumpeter; Money; Microeconomics; Methodology